Analysis of the mechanism of price and technological progress on economic fluctuations in resource-based areas: The case of Shanxi, China - Zhao, Zihang; Hernandez, Alexander A. (Edelweiss Applied Science and Technology, 2025)
This paper draws on the theory of the monetary economic cycle and the theory of the real economic cycle, constructs a theoretical model of economic fluctuations in resource-based regions that takes price levels and technological progress into consideration, analyzes the mechanism of the effect of price levels and technological progress on economic fluctuations in resource-based regions, and derives the key equation of the effect of the two on economic fluctuations. Then, taking Shanxi data as an example, the key equation is verified, and the Shanxi economy is analyzed through two econometric model methods, namely the time series threshold regression model and the Zou test, in two cases of static expectations and rational expectations. The necessity and path of the government's active regulation of economic transformation are proposed.